1989
DOI: 10.1128/aac.33.9.1428
|View full text |Cite
|
Sign up to set email alerts
|

Purification, toxicity, and antiendotoxin activity of polymyxin B nonapeptide

Abstract: Polymyxin B, a relatively toxic antibiotic, has potent endotoxin-neutralizing properties that may be beneficial as adjunctive therapy in gram-negative sepsis. Polymyxin B nonapeptide (deacylated polymyxin B) is devoid of antibiotic activity but retains the capacity to disorganize the outer membrane of gram-negative bacteria. To evaluate the potential therapeutic usefulness of this derivative, we produced purified polymyxin B nonapeptide, tested its in vivo toxicity in animals, and evaluated its in vitro antien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(111 citation statements)
references
References 52 publications
(54 reference statements)
1
110
0
Order By: Relevance
“…Polymyxin B, that binds to lipopolysaccharide and neutralizes its activity (Weinberg et al, 1978;Danner et al, 1989), has been reported to prevent spontaneous reduction of phenylephrine-induced tone possibly due to induction by lipopolysaccharide of an NO synthase (Rees et al, 1990a). Similarly, in the present experiments, polymyxin B also prevented development of L-arginine-induced relaxation, suggesting the possible induction of an NO synthase by lipopolysaccharide contamination of the Krebs solution which has been noted (Rees et al, 1990a).…”
Section: Discussionsupporting
confidence: 67%
“…Polymyxin B, that binds to lipopolysaccharide and neutralizes its activity (Weinberg et al, 1978;Danner et al, 1989), has been reported to prevent spontaneous reduction of phenylephrine-induced tone possibly due to induction by lipopolysaccharide of an NO synthase (Rees et al, 1990a). Similarly, in the present experiments, polymyxin B also prevented development of L-arginine-induced relaxation, suggesting the possible induction of an NO synthase by lipopolysaccharide contamination of the Krebs solution which has been noted (Rees et al, 1990a).…”
Section: Discussionsupporting
confidence: 67%
“…In particular, removal of the fatty acid chain by proteolytic cleavage with ficin or related enzymes resulted in deacylated nonapeptides [65], with less acute toxicity than their parent polymyxins along with a reduced antibacterial activity [66][67][68]. Despite lacking bactericidal activity themselves, these polymyxin nonapeptides (PMBN) can damage the outermost cell wall structure of Gram-negative bacteria, greatly increasing its permeability to hydrophobic antibiotics, which may facilitate combinatorial use with other antibiotics to treat specific infections [69][70][71][72][73][74][75].…”
Section: Polymyxins and Derivativesmentioning
confidence: 99%
“…The supernatants obtained after cell removal by centrifugation were assayed for PMB content by HPLC using a reversephase C 18 column (4.7 by 250 mm; YMC-Pack ODS-AM, YMC Inc.). Elution was carried out by increasing the content of acetonitrile from 0 to 100% in a mobile phase of 0.15% trifluoroacetic acid in H 2 O over 30 minutes at a flow rate of 1.0 ml/minute, and PMB was detected at an absorbance at 215 nm [23].…”
Section: Hplc Analysis Of Pmbmentioning
confidence: 99%